1989
DOI: 10.1002/cne.902840309
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from cortical blindness mediated by destruction of nontectotectal fibers in the commissure of the superior colliculus in the cat

Abstract: Transection of the commissure of the superior colliculus restores visual orientation behavior to a cat previously rendered hemianopic by a unilateral visual cortical lesion (the Sprague effect). Using two methods, we asked whether this recovery resulted from the severing of the tectotectal component of the commissure or whether the destruction of some other connection was responsible. First, we transected either the rostral or the caudal one-half of the tectal commissure in hemianopic cats. If destruction of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 73 publications
3
72
0
Order By: Relevance
“…We note that these uncertainties about double dissociation would not have been emphasized without the startling and paradoxical e¡ects of multiple inactivations, made apparent by careful studies of this system (e.g. Sprague 1966;Lomber & Payne 1996;Wallace et al 1989Wallace et al , 1990.…”
Section: (B) Single Dissociationmentioning
confidence: 96%
“…We note that these uncertainties about double dissociation would not have been emphasized without the startling and paradoxical e¡ects of multiple inactivations, made apparent by careful studies of this system (e.g. Sprague 1966;Lomber & Payne 1996;Wallace et al 1989Wallace et al , 1990.…”
Section: (B) Single Dissociationmentioning
confidence: 96%
“…These lesion data and the current findings require us to postulate a model in which covert orienting results from the balance among inhibitory, disinhibitory, and facilitatory influences within a distributed attentional system, including the lateral frontal cortex. The complex interplay among different components of such a system may be reminiscent of much better known oculomotor (Wallace et al, 1989(Wallace et al, , 1990) and motor systems (Alexander et al, 1986). Within such a model the absolute sign of the frontal blood flow difference is hard to interpret and may reflect inhibitory, disinhibitory, and facilitatory influences.…”
Section: Single Discriminations: Direction-sensitive Regionsmentioning
confidence: 99%
“…Many anatomical and behavioral studies on the collicular commissural connections have been devoted to showing the neural mechanism of the Sprague effect (Stein and Meredith 1993). However, more recent studies have shown that this effect is mediated by a pathway other than intrinsic collicular commissural neurons (CNs), because transection of the rostral commissure in the SC, where fibers of the intrinsic collicular CNs are known to run, produced no effect, whereas transection of the caudal commissure produced the Sprague effect (Wallace et al 1989(Wallace et al , 1990.…”
Section: Introductionmentioning
confidence: 99%